Scientometric Portrait of Dr. Jian Zhou, A Chinese Virologist and Co-Inventor of HPV Vaccine - Koley, Susanta; Goswami, Sutapa (Journal of Data Science, Informetrics, and Citation Studies, 2026)
The main aim of this study is to assess cervical cancer research related to Human Papillomavirus (HPV) infections, with a specific focus on the scientific contributions of Dr. Jian Zhou, a distinguished Chinese virologist whose pioneering work led to the development of the HPV vaccine. Using bibliometric techniques, this study quantitatively analyses his research output and evaluates his impact on the field of cervical cancer prevention. Cervical cancer, recognized since 400 BCE, was once considered untreatable. However, advances in medical research identified the Human Papillomavirus (HPV) as its primary cause. A major breakthrough occurred in 2006 with the introduction of the HPV vaccine, which significantly reduced cervical cancer risk. This monumental achievement is attributed to Jian Zhou and his collaborator, Ian Frazer, who developed the vaccines Gardasil and Cervarix. Zhou’s contributions have since been acknowledged as pivotal in global efforts to prevent cervical cancer. Data for this study were collected from 42 publications authored or co-authored by Zhou during his ten active research years, sourced primarily from Google Scholar and other databases. The information was organized and analysed using bibliometric methods to create a comprehensive profile of his research productivity. Findings reveal that Zhou published 42 papers on HPV, 26 of which appeared between 1990 and 1999, while 16 were posthumously published. All his works were co-authored, predominantly with Ian Frazer (40 joint papers). The majority of his publications (58.14%) were journal articles, with 12 appearing in Virology. His most cited paper (1991) received 774 citations. His productivity coefficient was 1, indicating steady research activity averaging 23 papers annually. This study, the first detailed bibliometric analysis of Jian Zhou’s contributions, offers valuable insights into his lasting impact on medical research, cancer immunology, and vaccine development.
Keywords: Bibliometrics; Bio-bibliometrics; Cancer Research; Cervical Cancer; Cervix Uteri; Female Cancer; Human Papillomavirus; Ian H Frazer; Informetrics; Jian Zhou; J. Zhou